(untitled) (Third Sector Social Economic Review, 2026)
The aim of the study is to reveal how the decision-making processes of individuals aged 18–35 are shaped within the framework of cognitive biases. In this context, the impact of common cognitive tendencies such as overconfidence, confirmation bias, and availability bias on individuals’ financial decisions and general decisions regarding their daily lives is examined. By analyzing the extent and nature of these biases’ influence on decision-making behavior, the research aims to contribute to understanding young adults’ capacity for rational decision-making. Thus, the study seeks to contribute to the literature at both theoretical and practical levels by evaluating the relationship between cognitive processes and decision outcomes from a holistic perspective. The data obtained within the scope of the research were collected through semi-structured interviews conducted face-to-face with 8 participants, and the interviews were systematically transcribed and analyzed. The transcribed recordings were coded using content analysis and evaluated within a thematic framework. The findings from the participants revealed that decision-making processes were not based solely on rational assessments; emotional factors and past experiences also played a significant role. Furthermore, confirmation bias and availability bias were found to influence which information individuals accessed and trusted. Based on the research findings, it has been concluded that cognitive biases often influence individuals’ decisions unconsciously and systematically. Although participants believed they made rational assessments in their decision-making processes, it was understood that cognitive tendencies such as overconfidence, confirmation bias, and availability bias guided their preferences and evaluations. In this context, it is considered that education and awareness-raising efforts aimed at increasing awareness of cognitive biases could contribute to individuals developing more critical and analytical thinking skills. It is suggested that structured educational programs, especially those targeting young adults, could support more consistent and rational choices in financial and general life decisions.